Role of natural productivity in growth performance and health of marron (Cherax cainii, Austin 2002) reared under semi-intensive aquaculture system and controlled laboratory conditions. - Tulsankar, Smita Sadanand (Curtin University, 2021)
The research from commercial marron ponds and laboratory–based experiments investigated the multi-facet interactions among seasons, plankton abundance and diversity with selected dissolved trace elements and finally their impact on marron yield, health and characterization of the gut microbiome. The results showed that trace element supplementation altered the plankton density, species diversity and marron gut microbiota and finally the presence of zooplankton in the culture system reflected the enhanced marron growth and health.